Brief Report: Use of Remnant Specimens to Assess Use of HIV PrEP Among Populations With Risk of HIV Infection: A Novel Approach. (1st August 2022) - Pathela, Preeti; Qasmieh, Saba; Gandhi, Monica; Rozen, Elliot; Okochi, Hideaki; Goldstein, Harris; Herold, Betsy C.; Jamison, Kelly; Schillinger, Julia A.; Nash, Denis
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: HIV-uninfected persons being evaluated for sexually transmitted infections (STIs) may be good HIV pre-exposure prophylaxis (PrEP) candidates. We measured PrEP use in a sentinel STI patient population. Design: Cross-sectional study, New York City Sexual Health Clinics (January 2019–June 2019). Methods: Remnant serum samples from 644 HIV-uninfected men who have sex with men (MSM) and 97 women diagnosed with chlamydia, gonorrhea, and/or early syphilis were assayed for tenofovir and emtricitabine levels using a validated liquid chromatography–mass spectrometry assay. Using paired test results and medical records, we assessed (1) prevalence and (2) correlates of PrEP use on the day of STI diagnosis (adjusted prevalence ratios [aPRs]). Results: PrEP use among 741 patients was 32.7% [95% confidence interval (CI): 29.3 to 36.0]; 37.3% for MSM and 2.1% for women. PrEP use was high among White MSM (46.8%) and lowest among women. Among MSM with rectal chlamydia/gonorrhea or early syphilis, PrEP use was associated with age [aPR = 1.7 (95% CI: 1.2 to 2.4) for ages 25–34 years and aPR = 2.0 (1.4 to 2.9) for ages 35–44 years, vs. 15 to 24 years]; number of recent sex partners [aPR = 1.4 (1.0 to 2.0) for 3–5 partners, aPR = 2.1 (1.5 to 3.0) for 6–10 partners, aPR = 2.2 (1.6 to 3.1) for >10 partners, vs. ≤2 partners]; having sex/needle-sharing partners with HIV [aPR = 1.4 (1.1–1.7)]; and inconsistent condom use [aPR = 3.3 (1.8–6.1)]. Race/ethnicity, past-year STI diagnosis, and postexposure prophylaxis use were not associated. Conclusions: One in 3 people with newly diagnosed STIs had detectable serum PrEP, and PrEP use was exceedingly rare among women. Routinely collected remnant samples can be used to measure PrEP use in populations at high risk of HIV acquisition.